Enhancing the Lifetime of Welded Joints Using the Protective Coating and Causes the Formation of Defects in Them; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Bezborodov V. P. Valery Pavlovich (2016, 2016)
Title screen